Religion and public life in the Pacific region: fluid identities - Roof, Wade Clark; Silk, Mark (Religion by region, 2005)
Preface / Mark Silk -- Introduction: Religion in the Pacific region / Phillip E. Hammond -- Religious affiliation in the Pacific region and the nation -- Religious self-identification and adherents claimed by religious groups, national and regional comparisons -- Religion in the Pacific region : demographic patterns / Wade Clark Roof -- Toward an established mysticism : judeo-Christian traditions in post-World War II, California and Nevada / Douglas Firth Anderson -- New players and new patterns / David W. Machacek -- The influence of alternative religions / Tamar Frankiel -- Pono and Kapu : righteousness and taboo in Hawaii / George J. Tanabe, Jr -- Conclusion: Faith and spirituality in a fluid environment / Wade Clark Roof.